Regaining Fiscal Sustainability and Enhancing Effectiveness in Croatia : A Public Expenditure and Institutional Review - World Bank (Washington, DC, 2013)
The report presents the macroeconomic setting, and fiscal developments in the 1990s in Croatia, a country facing an unparalleled opportunity towards sustainable growth, and integration into the European Union. Nonetheless, the country needs to sustain macroeconomic stabilization, and improve the investment climate. To this effect, public sector reform needs to be oriented to diminish the size of the state, and reduce the fiscal deficit to sustain macroeconomic stability in the medium term. Yet, the scope for reducing the deficit through revenue increases is limited, even though a decrease in the tax burden would be highly desirable. This means that most of the adjustment will need to be made in public expenditures, particularly by identifying, and implementing policies that will reduce the level of expenditures, while improving their effectiveness; thus, budgetary management improvement will be critical to this effort. The report analysis indicates that the current budget in Croatia is not a comprehensive measure of all fiscal activity, namely that five extra-budgetary funds are not included in the budget; that off-budget revenues, outside of the extra-budgetary funds, still exist; that the cash budgeting system leads to the accumulation of arrears that do not appear in budget presentations; and, that laws outside of the budget law, lead to mandatory spending that falls outside of the budget process.